Analisis Terhadap Problematika Pemeriksaan Bukti Permulaan Tindak Pidana Pajak Dalam UU Nomor 28 Tahun 2007 Tentang Ketentuan Umum dan Tata Cara Perpajakan Sebagaimana Telah Diubah Dengan Undang-Undang Nomor 7 Tahun 2021 - Takismen; Waldo, Risky (Rechtsregel : Jurnal Ilmu Hukum, 2024)
Examination of initial evidence in tax crimes is regulated in Article 43A of Law Number 7 of 2021 concerning Harmonization of Tax Regulations (UU HPP). Then the Elucidation to Article 43A paragraph (1) states. "Information, data, reports and complaints received by the Directorate General of Taxes will be developed and analyzed through intelligence activities and/or other activities whose results can be followed up with an Audit, Preliminary Evidence Examination, or not followed up. Preliminary Evidence Examination has the same objectives and status as investigations as regulated in the law governing criminal procedural law. Looking at the provisions in Article 1 paragraph (5) of the Criminal Procedure Code, it explains, "Investigation is a series of investigative actions to search for and discover an incident that is suspected of being a criminal act in order to determine whether or not an investigation can be carried out according to the method regulated in this law." This has the consequence that examining evidence of the beginning of criminal acts in the field of taxation has the same objectives and position as investigations regulated in law, of course the law in question is Law Number 8 of 1981 concerning the Criminal Procedure Code. The type of research used by the author is normative juridical using secondary data consisting of primary legal materials, namely the Criminal Procedure Code, the HPP Law, other regulations as well as secondary legal materials, namely relevant books and journals. Data analysis uses qualitative descriptive and systematic interpretation. The results of the research show that the initial evidence examination process carried out by the Directorate General of Taxes (DJP) for Taxpayers can be carried out as a pre-trial effort. In the event that a Preliminary Evidence Audit Order has been issued, the taxpayer can check the identity of the official who signed and issued the letter and if there are incorrect procedures carried out by the DJP Civil Servant Investigator (PPNS), the taxpayer can submit legal action, namely Pre-Trial to District Court.